Role of CYP17 rs743572 Polymorphism in Benign Prostatic Hyperplasia: A Multivariate Integrated Analysis - Weng, Hong; Fang, Cheng; Geng, Pei-Liang; Jin, Ying-Hui; Zeng, Xian-Tao; Wang, Xing-Huan (Frontiers in Physiology, 2019)
Objective: Many published studies investigated the association between CYP17 rs743572 polymorphism and benign prostatic hyperplasia (BPH) but yielded inconsistent results. Hence, we performed this meta-analysis using the multivariate statistic method. Methods: Case-control or cohort studies with adequate genotype distribution or minor allele frequency (MAF) were identified by searching the PubMed and Embase databases up to March 15, 2015. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the association between CYP17 rs743572 polymorphism and BPH susceptibility. Results: Pooled MAFs of 13 studies were 37% in Caucasians and 56% in Orientals, respectively. Pooled results of 8 studies suggested that CYP17 rs743572 was not associated with the BPH susceptibility in the overall population (OR = 0.98, 95% CI: 0.80-1.20 for A2 vs. A1; OR = 0.99, 95% CI: 0.79-1.25 for A1/A2 vs. A1/A1; OR = 0.97, 95% CI: 0.62–1.53 for A2/A2 vs. A1/A1). Sensitivity analysis showed the results were robust. Subgroup analyses suggested that A2 allele carriers had a 28% lower risk of developing BPH as compared with A1 allele carriers, and the risk of BPH is 47% lower inA2/A2 genotype carriers as compared with A1/A1 genotype carriers. We did not observe any significant association in Caucasians. Conclusion: In conclusion, our study indicates a negative association between CYP17 and BPH in Orientals.